Annotated List of the Family Lygaeidae Schilling, 1829 (Heteroptera) in Libya - El Meghrai, Moftah Soliman (Al-Mukhtar Journal of Sciences, 2020)
In this study, subfamilies, genera, and species of Lygaeidae are given, accompanied by synonyms, local and general distribution. This study was carried out during the years 2007-2010 in the country of Libya. This study revealed the presence of 111 species in Libya under 52 genera to 8 subfamilies. 31 are recoded from Libya for the first time in the present study.